Community Empowerment through Agricultural Waste-Based Bio-Briquette Production for Renewable Energy - Susi Indriani (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This community service program aimed to empower residents of Attangsalo Village, Ma'rang Subdistrict, Pangkep Regency, to convert locally abundant rice husk and pomelo peel waste into bio-briquettes as an alternative renewable energy source. The program was implemented through four stages: preliminary field assessment, community education, hands-on training, and program evaluation. A distinctive feature of this initiative was the integration of two underutilized agricultural wastes into a community-based renewable energy solution, promoting both waste valorization and environmental sustainability. Program effectiveness was evaluated using pre-test and post-test questionnaires, direct observation, and participant interviews. The average knowledge score increased from 49% in the pre-test to 100% in the post-test, while more than 90% of participants successfully produced functional bio-briquettes independently following the training. Participants also demonstrated improved technical skills and expressed strong interest in adopting the technology for household use and small-scale enterprises. Overall, the program enhanced community capacity in agricultural waste management, promoted renewable energy awareness, and created opportunities for sustainable local economic development through bio-briquette production.